2012
DOI: 10.1007/s12149-012-0576-5
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function–morphologic relationships assessed by SPECT–CT fusion images

Abstract: Pulmonary single photon emission computed tomography-computed tomography (SPECT-CT) fusion images provide objective and comprehensive assessment of pulmonary function and morphology relationships at cross-sectional lungs. This article reviewed the noteworthy findings of lung pathophysiology in wide-spectral lung disorders, which have been revealed on SPECT-CT fusion images in 8 years of experience. The fusion images confirmed the fundamental pathophysiologic appearance of lung low CT attenuation caused by airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
5
0
2
Order By: Relevance
“…reported that attenuated mosaic pattern of the chest on CT images is related to pulmonary vascular disease and obstructive airway disease. In particular, low‐attenuation areas are associated with perfusion defects on perfusion SPECT/CT images, presumably due to the hypoxic vasoconstriction induced by perfusion defects, which decreases the diameter or volume of the peripheral vasculature . Convolutional neural networks (CNNs) can be used to capture and learn from this structural information of images.…”
Section: Discussionmentioning
confidence: 99%
“…reported that attenuated mosaic pattern of the chest on CT images is related to pulmonary vascular disease and obstructive airway disease. In particular, low‐attenuation areas are associated with perfusion defects on perfusion SPECT/CT images, presumably due to the hypoxic vasoconstriction induced by perfusion defects, which decreases the diameter or volume of the peripheral vasculature . Convolutional neural networks (CNNs) can be used to capture and learn from this structural information of images.…”
Section: Discussionmentioning
confidence: 99%
“…Daha fazla çalışmaya ihtiyaç olmakla birlikte, sadece perfüzyon SPECT/BT'nin ventilasyon çalışmasına ihtiyacı ortadan kaldırmadığı söylenebilir (15,24). SPECT/ BT'den elde edilen füzyon görüntüleri ile kronik obstrüktif akciğer hastalığı, interstisyel akciğer hastalığı gibi akciğer hastalıklarında, BT'de normal görülen akciğer alanlarında beklenmedik perfüzyon defektleri gösterilmiştir (25). Her iki görüntüleme yöntemi ile elde edilen şüpheli bulgular, hibrit görüntüleme ile birlikte değerlendirilerek aydınlatılabilir.…”
Section: Pulmonerembolitanısındaventilasyonperfüzyon Tekfotonemisyontunclassified
“…Akciğer kanserli hastaların radyoterapi planlamasında, V/P SPECT kullanılmasının radyasyon doz maruziyetini azaltarak radyasyona bağlı akciğer komplikasyonlarının önlenmesine katkı sağladığı gösterilmiştir (16,17). V/P SPECT/BT'nin kantitatif akciğer çalışmalarına da katkı sağlayabileceği gösterilmiştir; atenüasyon ve saçılma düzeltmesi yapılmış SPECT/BT görüntüleri ile bölgesel akciğer fonksiyonları daha doğru hesaplanabilir (25). Gelecekte akciğerin fonksiyonel ve morfolojik verilerinin bir arada değerlendirilmesine imkân sağlayan füzyon görüntüleri, değişik akciğer bozukluklarına ait patofizyolojilerin daha kapsamlı anlaşılmasına yol açacaktır.…”
Section: Diğer Akciğer Ventilasyon Perfüzyon Tek Foton Emisyon Tomogrunclassified
“…Single photon emission computed tomography (SPECT) is a variation in CT in which gamma rays emitted from an injected radionuclide source are detected by a rotating gamma camera (56). The technique allows for three-dimensional reconstruction, and when used with specific radioligands, tissues of interest can be closely scrutinized.…”
Section: Specific Classes Of Pulmonary Hypertension Biomarkersmentioning
confidence: 99%